The role of pre‐operative imaging and double balloon enteroscopy in the surgical management of small bowel neuroendocrine tumors: Is it necessary?. Issue 2 (20th September 2017) - Manguso, Nicholas; Gangi, Alexandra; Johnson, Jeffrey; Harit, Attiya; Nissen, Nicholas; Jamil, Laith; Lo, Simon; Wachsman, Ashley; Hendifar, Andrew; Amersi, Farin
Abstract : Background and Objectives: Pre‐operative localization of small bowel neuroendocrine tumors (SBNET) is important for operative planning. The aim was to determine the effectiveness of pre‐operative imaging and double‐balloon enteroscopy (DBE) in identifying extent of disease. Methods: Database review identified 85 patients with primary SBNET between 2006 and 2013. Analysis included patients who underwent imaging, endoscopy, and surgery at our institution. Results: Average age was 60.7 years. Sixty‐six (77.1%) patients had a primary NET in the ileum. Seventy‐two patients (67.3%) underwent CT, 47 (46.7%) had MRI, 44 (46.7%) had somatostatin receptor imaging (SRI), and 41 (39.3%) underwent DBE. The sensitivity of each in identifying the NET was 59.7% for CT, 54% for MRI, 56% for SRI, and 88.1% for DBE. Eighteen (21.2%) patients had primary tumors not identified on imaging. Of these 18, 13 underwent DBE, and 12 of 13 (92.3%) DBEs identified the primary lesion. DBE was significantly better at identifying the primary NET than CT, MRI or SRI ( P  = 0.004, 0.007, and 0.012). Conclusions: Most SBNETs are identified with a combination of imaging modalities. In those with unidentified primary tumors after imaging, DBE should be considered as it may provide valuable information as to the location of the primary tumor.